Primary Neuroendocrine Tumor of the Breast: Current Understanding and Future Perspectives - Sun, Hongna; Dai, Shuang; Xu, Junnan; Liu, Linan; Yu, Jiaxing; Sun, Tao (Frontiers in Oncology, 2022)
Primary neuroendocrine carcinoma of the breast (NECB) is a heterogeneous, rare, poorly differentiated, and probably underestimated subtype of breast cancer, including small cell NECs and large cell NECs. The diagnostic criteria have been updated many times because of constant changes and deepening understanding of the disease. Primary neuroendocrine neoplasms (NEN) of the breast consist of well-differentiated neuroendocrine tumors (NET), highly aggressive neuroendocrine carcinomas (NEC) as well as invasive breast cancers of no special type (IBCs-NST) with neuroendocrine differentiation according to the latest WHO classification. Due to the low incidence of NECB, its correct diagnosis remains a challenge, which needs multi-disciplinary methods. For the rarity of the disease, there is a lack of large samples and prospective clinical research. For these invasive tumors, there are no standardized therapeutic guidelines or norms, and treatment often refers to nonspecific breast cancer. And information on the prognosis of such patients remains confusing. In 2003, World Health Organization (WHO) listed NECB as an independent entity for the first time, while many features of NECB remain to be clarified. Therefore, this review presents the WHO classification, clinicopathologic characteristics, diagnosis, treatment and prognosis of these patients. In addition, we summarize the latest studies on molecular features of NECB to provide new therapeutic perspectives.